2021
DOI: 10.3390/brainsci11091203
|View full text |Cite
|
Sign up to set email alerts
|

Early Right Motor Cortex Response to Happy and Fearful Facial Expressions: A TMS Motor-Evoked Potential Study

Abstract: The ability to rapidly process others’ emotional signals is crucial for adaptive social interactions. However, to date it is still unclear how observing emotional facial expressions affects the reactivity of the human motor cortex. To provide insights on this issue, we employed single-pulse transcranial magnetic stimulation (TMS) to investigate corticospinal motor excitability. Healthy participants observed happy, fearful and neutral pictures of facial expressions while receiving TMS over the left or right mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 80 publications
7
64
1
Order By: Relevance
“…Ellena et al confirm the defensive functional definition of IPS by emphasizing how responses to approach stimuli modulate autonomic arousal as a function of the distance between the perceiver and the stimuli, resulting in an appropriate organization of defensive reactions [ 15 ]. The use of single-pulse transcranial magnetic stimulation to explore the temporal sequence of the motor system output to relevant arousing stimuli proved to be of great value, reflecting the preparation of adaptive motor responses required for the execution of appropriate and protective behaviors [ 16 ]. Moreover, it is worth noting the many other contributing factors for increased stress, like the threat of contracting the virus, infection or death of loved ones, loneliness because of social isolation, quarantine measures, financial instability, and poverty as a result of huge job loss, and last but not least excessive consumption of information from the media.…”
Section: Introductionmentioning
confidence: 99%
“…Ellena et al confirm the defensive functional definition of IPS by emphasizing how responses to approach stimuli modulate autonomic arousal as a function of the distance between the perceiver and the stimuli, resulting in an appropriate organization of defensive reactions [ 15 ]. The use of single-pulse transcranial magnetic stimulation to explore the temporal sequence of the motor system output to relevant arousing stimuli proved to be of great value, reflecting the preparation of adaptive motor responses required for the execution of appropriate and protective behaviors [ 16 ]. Moreover, it is worth noting the many other contributing factors for increased stress, like the threat of contracting the virus, infection or death of loved ones, loneliness because of social isolation, quarantine measures, financial instability, and poverty as a result of huge job loss, and last but not least excessive consumption of information from the media.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, interindividual differences may potentially account for this lack of effect for positive pictures in ERP responses in our study, especially since a recent study by the Ref. [ 53 ] has shown that interindividual differences can predict how one will perceive and respond to emotional information.…”
Section: Discussionmentioning
confidence: 93%
“…Research has focused on classifying and predicting emotion dimensions while participants perform in externally driven activities, including watching video clips, facial pictures, and sequences of images [ 65 , 218 , 219 ]. In addition to exposure to these external stimuli, expression of the basic innate emotions (i.e., fear, anger, surprise, sadness, happiness, and disgust) causes different behavioral responses in individuals [ 220 , 221 ], Notably, fearful facial expression is a threatening stimulus resulting in an appropriate organization of defensive responses [ 222 ]. Moreover, environmental factors, such as approaching direction [ 223 ] have contributed to clarifying the effects of behavioral responses (i.e., defensive responses).…”
Section: Discussionmentioning
confidence: 99%